Previdism In Science and Previdism about Science - Szynkiewicz, Mariusz (Studia Oeconomica Posnaniensia, 2017)
Predicting treated in the context of scientifi c products and scientifi c activity in a broad sense is a complex and multidimentional phenomenon. Firstly, it can refer to scientifi c products (e.g. laws and theories) as well as to science understood as a given type of social activity. Secondly, the idea of prediction should be analysed as temporary and not referring only to the future (future imperfect phenomena) but with respect to the past (postgnosis, retrodiction) and present (diagnosis) phenomena. Thirdly, due to span criteria, science related predictions can be divided into detailed ones, referring to scientifi c products and general ones.